2015
DOI: 10.1016/j.jbi.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

A novel neural-inspired learning algorithm with application to clinical risk prediction

Abstract: Clinical risk prediction - the estimation of the likelihood an individual is at risk of a disease - is a coveted and exigent clinical task, and a cornerstone to the recommendation of life saving management strategies. This is especially important for individuals at risk of cardiovascular disease (CVD) given the fact that it is the leading causes of death in many developed counties. To this end, we introduce a novel learning algorithm - a key factor that influences the performance of machine learning-based pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…The accuracy of the proposed method was 97.833%. Tay et al (2015) propose a new supervised learning algorithm, the artificial neural cell system for classification (ANCSc), which is used for predicting the risk of developing cardiovascular diseases. The algorithm is inspired by the human learning process that is based on three neural processes occurring in the brain: neurogenesis, neuroplasticity, and apoptosis.…”
Section: Related Workmentioning
confidence: 99%
“…The accuracy of the proposed method was 97.833%. Tay et al (2015) propose a new supervised learning algorithm, the artificial neural cell system for classification (ANCSc), which is used for predicting the risk of developing cardiovascular diseases. The algorithm is inspired by the human learning process that is based on three neural processes occurring in the brain: neurogenesis, neuroplasticity, and apoptosis.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Fonarow et al, developed a classification and regression tree for risk stratification of patients hospitalized with the Acute Decompensated Heart Failure (ADHF). Their experimental results revealed that ADHF patients at low-, medium-, and highrisk for in-hospital mortality can be easily identified using vital sign and laboratory data obtained on hospital admission [22]. Wang et al, extended the linear regression model for risk stratification that provides clinicians with not only the accurate assessment of a patient's risk but also the clinical context to be acted upon [7].…”
Section: Related Workmentioning
confidence: 99%
“…A computer system is being developed for obtaining and storing information, extracting knowledge from databases, predicting the risk of adverse outcomes with elements of training the system based on neural networks by analogy with natural neurogenesis, apoptosis, neuroplasticity [118,119].…”
Section: Introductionmentioning
confidence: 99%